Evaluation of blended learning during Corona pandemic from the point of view of teachers and principals of public schools in Jerusalem governorate - Inairat, Iman Ali Obaydieh; Barham, Kifah Ahmad (Journal of Educational and Psychological Sciences, 2023)
This study evaluated teachers and principals’ attitudes on the success of blended education program during COVID-19 pandemic at public schools in Jerusalem Governorate. The researcher adopted the descriptive analytical approach to achieve the research objectives. The researcher proposed a list of criteria for evaluating the blended education program implemented during COVID-19 pandemic at Jerusalem public schools. These proposed criteria were presented to a focus group consisting of educational supervisors and experienced teachers to evaluate, and then converted to questionnaire items. The questionnaire latter on was referred by a number of juries specialized in teaching methods and educational administration. Furthermore, the questionnaire was piloted on 30 individuals who were excluded from the sample in order to verify its validity and reliability. The study recruited 103 male and female teachers, and 43 principals, who were selected by random sampling method. Results: The degree of agreement of the study sample on the availability of the proposed standards for evaluating blended learning was medium for all standards. The level of availability of the standards was medium for all. There is a statistically significant difference between the responses of the study sample on the proposed criteria for evaluating blended learning in light of the Corona pandemic, according to the gender variable, in favor of females, as well as according to the educational qualification variable. There are differences according to the years of experience variable, and in favor of the category (15 years and over). The study sample on the proposed standards according to the job title variable. In light of the results of the study; The researcher recommended the necessity of identifying the competencies that would lead to the success of the blended learning program.